Moral Education for Youth in the Modern Era Perspective of Abdullah Nashih Ulwan - Yuli Habibatul Imamah; Duski Ibrahim; Akmal Hawi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to analyze Abdullah Nashih Ulwan's thoughts on adolescent moral education in Islam in the modern era and its relevance in answering the problems of adolescent life. This research is a library research with the main source of the book Tarbiyah al-Aulad fi al-Islam written by Abdullah Nashih Ulwan. The analysis technique uses content analysis. This study found that first, five methods of moral education, namely the exemplary method; habituation; advice; attention and monitoring; and punishment. Second, deviations that occur in adolescents are caused by poverty, orphanage disasters, parental disharmony, divorce, poor parental treatment and example, excessive pampering of children, favoritism towards children, neglect of children's education, and negative associations. Third, the solution to the problems of Muslim youth is to provide religious education, provide a decent life, give responsibility for freedom, make teenagers comfortable, spend time together, and become friends.